PATRIOTISM IN THE SYSTEM OF INTERESTS OF MODERN PEOPLE - Zinaida V. Bragina; Elena V. Ponomarenko (Статистика и экономика, 2016)
The social and economic role of patriotismin the socio-economic progress of Russiais considered in the article. The comparative analysis of technologies of formation ofpatriotism in the United States, Israel andFrance is provided. The role of the general and vocational education system in this process is deﬁned. The system of measures to mainstream the patriotism of the populationof Russia is proposed.